Design of a nanoplatform for treating pancreatic cancer - Manawadu, Harshi Chathurangi (Kansas State University, 2014)
Pancreatic cancer is the fourth leading cause of cancer-related deaths in the USA. Asymptomatic early cancer stages and late diagnosis leads to very low survival rates of pancreatic cancers, compared to other cancers. Treatment options for advanced pancreatic cancer are limited to chemotherapy and/or radiation therapy, as surgical removal of the cancerous tissue becomes impossible at later stages. Therefore, there's a critical need for innovative and improved chemotherapeutic treatment of (late) pancreatic cancers. It is mandatory for successful treatment strategies to overcome the drug resistance associated with pancreatic cancers. Nanotechnology based drug formulations have been providing promising alternatives in cancer treatment due to their selective targeting and accumulation in tumor vasculature, which can be used for efficient delivery of chemotherapeutic agents to tumors and metastases. The research of my thesis is following the principle approach to high therapeutic efficacy that has been first described by Dr. Helmut Ringsdorf in 1975. However, I have extended the use of the Ringsdorf model from polymeric to nanoparticle-based drug carriers by exploring an iron / iron oxide nanoparticle based drug delivery system. A series of drug delivery systems have been synthesized by varying the total numbers and the ratio of the tumor homing peptide sequence CGKRK and the chemotherapeutic drug doxorubicin at the surfaces of Fe/Fe₃O₄-nanoparticles. The cytotoxicity of these nanoformulations was tested against murine pancreatic cancer cell lines (Pan02) to assess their therapeutic capabilities for effective treatments of pancreatic cancers. Healthy mouse fibroblast cells (STO) were also tested for comparison, because an effective chemotherapeutic drug has to be selective towards cancer cells. Optimal Experimental Design methodology was applied to identify the nanoformulation with the highest therapeutic activity. A statistical analysis method known as response surface methodology was carried out to evaluate the in-vitro cytotoxicity data, and to determine whether the chosen experimental parameters truly express the optimized conditions of the nanoparticle based drug delivery system. The overall goal was to optimize the therapeutic efficacy in nanoparticle-based pancreatic cancer treatment. Based on the statistical data, the most effective iron/iron oxide nanoparticle-based drug delivery system has been identified. Its Fe/Fe₃O₄ core has a diameter of 20 nm. The surface of this nanoparticle is loaded with the homing sequence CGKRK (139-142 peptide molecules per nanoparticle surface) and the chemotherapeutic agent doxorubicin (156-159 molecules per surface), This nanoplatform is a promising candidate for the nanoparticle-based chemotherapy of pancreatic cancer.
Keywords: Iron Oxide Nanoparticle; Pancreatic Cancer; Response Surface Methodology; Chemistry (0485); Chemistry, Pharmaceutical (0491)